Influence of Awe on Green Consumption: The Mediating Effect of Psychological Ownership - Wang, Liying; Zhang, Guangling; Shi, Pengfei; Lu, Xingming; Song, Fengsen (Frontiers in Psychology, 2019)
The increasing demand for environmental protection has given rise to burgeoning research on green consumption. The present research adds to this expanding literature by investigating a novel predictor of consumer green consumption: awe. As a self-transcendent emotion, awe arises when people encounter perceptually vast stimuli that overwhelm their existing knowledge and mental structures, and, meanwhile, this also elicits a need for accommodation. This research proposes and demonstrates that, compared with happiness and a neutral affective state, experience of awe promotes green consumption via an enhanced psychological ownership of nature. Moreover, this research identifies a condition by showing that, while awe promotes green consumption when interdependent self-construal is activated, this effect diminishes when independent self-construal is activated.